Thermo-Physical Properties And Mathematical Modeling Of Thin-Layer Drying Kinetics Of Medium And Long Grain Parboiled Rice - Bualuang, Oraporn; Tirawanichakul, Supawan; Tirawanichaku, Yutthana (ASEAN Journal of Chemical Engineering, 2011)
This research was to investigate some thermo-physical properties and to determine a mathematical model for describing drying kinetics for medium and long grain parboiled rice varieties. The thermo-physical properties in terms of equilibrium moisture content (EMC), apparent density, void fraction, specific heat capacity at moisture content ranging from 30 to 58% dry-basis (d.b.) for both Leb Nok Pattani (LNP) and Suphanburi 1 (SP 1) rice varieties were determined by conventional standard techniques.The evaluated results showed that EMC values for both rice varieties predicted by the GAB’s model yielded the best fitting with experimental data. To determine thermo-physical properties, the results stated that apparent density and specific heat capacity of parboiled LNP and SP1 rice varieties were linearly dependent on moisture content. In contrast, percentage of void fraction of medium grain LNP and long grain SP1 rice variety was inversely proportional to moisture content. For employing empirical thin-layer drying models, the Two terms model was the best fitting model to describe the experimental data for both rice varieties.